Collaboration in Frontline Health Care Delivery: Examining the Contractual Relationship Between Local Governments and Emergency Medical Services Agencies - Bromberg, Daniel E.; Henderson, Alexander C. (American review of public administration, 2015)
Contracting for complex human services has presented the field of public administration with a number of difficult and enduring questions. Emergency medical services (EMS) provide an ideal arena for further investigation into this topic. We utilize a relational contracting framework to examine key questions associated with trust in the collaborative provision of EMS. The findings indicate that contract specificity, provider performance, and administrative professionalization influence trust in these relationships.